Novel three-dimensional carbon nanotube networks as high performance thermal interface materials - Kong, Qinyu (2018)
Vertically aligned carbon nanotube (VACNT) arrays are considered as promising thermal interface materials (TIMs) due to their superior out-of-plane thermal conductivities. However the air gaps between adjacent CNTs within the CNT array hinder the in-plane heat transfer, thus significantly degrading the thermal performance of VACNT-based TIMs. To improve the in-plane thermal conduction of VACNT arrays, we propose a novel three dimensional CNT (3D CNT) network structure, where VACNTs are cross-linked by randomly-oriented secondary CNTs. Three different catalyst preparation methods for the secondary CNT growth are compared in terms of their ability to produce a dense network of secondary CNTs. The 3D CNT network grown using the chemical impregnation method shows a denser network structure, and thus is chosen for further thermal characterization. The temperature fields of the corresponding 3D CNT network under different heating powers are recorded using a 15 μm-resolution infrared thermal imaging system. The in-plane thermal conductivity is then derived from these fields using numerical fitting with a 3D heat diffusion model. We find that the in-plane thermal conductivity of the 3D CNT network is 5.40 ± 0.92 W/mK, at least 30 times higher than the thermal conductivity of the primary VACNT array used to grow the 3D CNT network.